Identification of Differential Genes of DNA Methylation Associated With Alzheimer’s Disease Based on Integrated Bioinformatics and Its Diagnostic Significance - Chen, Fan; Wang, Na; He, Xiaping (Frontiers in Aging Neuroscience, 2022)
Background: Alzheimer's disease (AD) is a common neurodegenerative disease . The pathogenesis is complex and has not been clearly elucidated, and there is no effective treatment. Recent studies have demonstrated that DNA methylation is closely associated with the pathogenesis of AD, which sheds light on investigating potential biomarkers for the diagnosis of early AD and related possible therapeutic approaches. Methods: AD patients samples and healthy controls samples were collected from 2 datasets in the GEO database. Using LIMMA software package in R language to find differentially expressed genes (DEGs). Afterwards, DEGs have been subjected to enrichment analysis of GO and KEGG pathways. The PPI networks and Hub genes were created and visualized based on the STRING database and Cytoscape. ROC curves were further constructed to analyze the accuracy of these genes for AD diagnosis. Results: Analysis of the GSE109887 and GSE97760 datasets showed 477 significant DEGs. GO and KEGG enrichment analysis showed terms related to biological processes related to these genes. The top ten Hub genes were found on the basis of the PPI network using the CytoHubba plugin, and the AUC areas of these top ranked genes were all greater than 0.7, showing satisfactory diagnostic accuracy. Conclusion: The study identified the top 10 Hub genes associated with AD-related DNA methylation, of which RPSA, RPS23, and RPLP0 have high diagnostic accuracy and excellent AD biomarker potential.